Legal Protection in Retail Financial Markets - Carlin, Bruce Ian; Gervais, Simon (The Review of Corporate Finance Studies, 2012)
We model a retail financial institution that outsources its advice services to an intermediary, making the two parties jointly responsible for consumers' experience with the products. In this context, courts that enforce state-contingent legal rules are necessary in order to avoid market breakdowns. To maximize social welfare, the government implements a system of penalties that depends on product characteristics and on the firm's relative ability to control quality. This legal system emphasizes reliable advice over transaction pace. Furthermore, the implicit team structure of the firm and its intermediary prevents self-regulation from achieving the same social efficiency. (JEL G18, G28, D11, D18, L51, K20)